INSTITUTIONAL CHANGE AT LOCAL LEVEL: HOW GILI INDAH VILLAGERS BUILD AN EFFECTIVE LOCAL GOVERNANCE OF CORAL REEF MANAGEMENT? - Aceng Hidayat (JOURNAL OF COASTAL DEVELOPMENT, 2005)
This paper aims at explaining the process of institutional change in coral reef management at the village level, and mainly seeks to answer two research questions: How do the processes of local institutional change take place? What are incentives that drive local communities to participate in them? Investigations in Gili Indah village, West Lombok Indonesia show that the process of the institutional change was initiated and done by villagers whose livelihood strongly depend on coral reef ecosystems. There are also strong indications that the changes were affected by the local and external economic conditions, which inevitably force resource users and economic actors to alter their economic strategies. The entering of industrial tourism and the emergence of tourism-related livelihoods in Gili Indah has driven economic actors to adapt to the altering environmental condition. Tourism Business Operators (TBO) and fishermen, two main actors, have played important roles in the change process. TBOs, whose livelihood depends on coral reef ecosystems, have a strong interest in protecting the ecosystems from degradation. The same goes for the fishermen, who claim themselves as main beneficiaries of coral reef ecosystems, and insist on maintaining the status quo as an attempt to protect their economic interest. Two different economic interests have been incentive for an evolution process of local institutions (awig-awig) to construct a governance structure that accommodates the varied economic interest. So far, this governance structure has been effectively forcing the actors to comply with the rules that drive themselves to use the coral reef ecosystems in a sustainable way.